Hydrogen-Containing Fuel Influence on Compression-Ignition Engine Part Wear and Emissions of Toxic Substances - Alexander I. Balitskii; Tomasz K. Osipowicz; Karol F. Abramek; Valentina O. Balitska; Paweł Kochmański; Marcin A. Królikowski (Energies)
Issues related to the components of modern fuel equipment wear processes have been discussed. The fuel injector is one of the key elements of the fuel equipment system, because it is a device responsible for distributing and spraying hydrogen-containing fuel in the engine combustion chamber. It is mounted in the modern engine head directly in the combustion chamber. If the fuel injector is faulty, it affects the operating parameters and in particular the ecological parameters of the modern engine, such as the emission of toxic substances into the environment. Additionally, a hydrogen reactor has been installed in the Common Rail (CR) system, the task of which is to produce hydrogen. As a result of the temperature prevailing in the operating environment of the injection equipment, various types of wear occur inside the system, including hydrogen degradation. The types of degradation processes of precision pairs of modern fuel injectors have been analyzed and classified. Microscopic tests were performed to analyze the contamination in the fuel system and to compare the ecological parameters of the engine operating on efficient and worn fuel injectors. The emission of nitrogen oxides, carbon monoxide and soot has been analyzed as a key ecological parameter. It has been established that the loss of precision of pairs of elements of a damaged fuel injector significantly affects the size of the injection doses of the fuel mixture containing hydrogen.